Олий таълим муассасалари талабаларининг жисмоний маданиятини ривожлантириш масалалари - Аҳмедов, Ф.Қ.; Кулбоев, Н.С. (SCIENCE and SOCIETY, 2020)
The article outlines the areas of physical culture of students of higher educational establishments. It also contains scientific information aimed at identifying existing problems in the students, physical culture.